The study of THz vertical cavity SASER devices - Wan Ahmad Kamil, Wan Maryam (2013)
In this thesis, experimental evidence of sustained phonon oscillations, from an electrically pumped vertical-cavity SASER device, working in the THz frequency domain is presented. Experimental investigation of injection seeding of phonons at a particular frequency, by optical excitation, is also presented. The experimental evidence of phonon oscillation through SASER action consists of a non-linear increase in the initial rising edge of the ballistically propagating LA phonons signal and an increased directionality of emission, once threshold gain is exceeded. The build-up of phonon oscillation fitted well with the theoretical model, also discussed in this thesis, enabling other attributes of the SASER device such as the gain coefficient, maximum acoustic power and device efficiency to be obtained. The cavity was investigated by means of pump-probe reflectivity measurements. Good quantitative agreement is obtained for the cavity mode frequencies, compared to the calculated reflectance of the cavity modes. Good quantitative agreement of the phonon scattering losses, within the cavity, was also obtained, when compared with theoretical predictions. Also provided is experimental evidence of injection seeding in the SASER devices under different conditions. The SASER device yields analogous characteristics to a seeded laser in that it acts as a phonon amplifier, due to SASER action, for the injected modes. The results contribute not only towards understanding the fundamental principles of achieving SASER oscillations but also towards the possibility of achieving a practical SASER device in the future.